Smart shape-controlled synthesis of poly(N-isopropylacrylamide)/chitosan/Fe3O4 microgels. (May 2015) - Sun, Minmin; Zhu, Aimei; Zhang, Qiugen; Ye, Meiling; Liu, Qinglin
Graphical abstract: Highlights: Smart shape-controlled PNIPAM/CS/Fe3 O4 microgels were flexibly synthesized. The as-prepared microgels possessed of spindle-shaped, cuboid and spherical shapes. The microgels exhibited good magnetic, thermo- and pH-sensitivities. The microgels show a great promise in bioseparation and many other fields. Abstract: A novel approach was developed to synthesize smart shape-controlled PNIPAM/CS/Fe3 O4 microgels with uniform size. Interestingly, the microgels in spindle-shaped, cuboid and spherical morphologies were successfully prepared using the micro-emulsion polymerization at a low temperature from 28 to 40 °C based on the theory of "coil-to-globule". The morphology and properties of the as-prepared products were investigated using scanning electron microscope (SEM), dynamic light scattering (DLS) and superconducting quantum interference device (SQUID). Results revealed that the PNIPAM/CS/Fe3 O4 microgels exhibited good thermo- and pH-sensitivities, and the size of the microgels decreased sharply upon increasing the temperature around 32 °C. The microgels with various shapes show a great promise in bioseparation and many other fields in the future.